Efektivitas Gugatan Warga PTUN dalam Menguji Legalitas PBG Star Padel Pulomas - Oktavianus Abrianta Sembiring (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2026)
This study examines community control mechanisms over State Administrative Decisions (KTUN) in the licensing sector through a case study of a citizens' lawsuit against the issuance of a Building Approval (PBG) for the commercial padel court